The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.31219/osf.io/24w5p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Repurposing of FDA Approved Drugs Against Monkeypox Virus Cysteine Proteinase: A Molecular Docking and Dynamics Simulation Study.

Abstract: Monkeypox is a zoonotic disease caused by a DNA virus known as Monkeypox virus. Generally, Monkeypox disease is considered a self-limiting condition with symptoms similar to that of smallpox disease. Most cases of Monkeypox are considered mild but some patients may suffer from serious complications. Due to the high similarity between Monkeypox virus and smallpox virus, therefore vaccines and antiviral therapies originally intended for use against smallpox can be effective also in Monkeypox infection cases. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…It was found that dihydroergotamine showed efficient binding with the proteins and inhibited Mpox cysteine proteinase. These findings support further in-vitro and in-vivo studies on dehydroergotamine for potential therapy against Mpox [60].…”
Section: Dihydroergotaminesupporting
confidence: 83%
“…It was found that dihydroergotamine showed efficient binding with the proteins and inhibited Mpox cysteine proteinase. These findings support further in-vitro and in-vivo studies on dehydroergotamine for potential therapy against Mpox [60].…”
Section: Dihydroergotaminesupporting
confidence: 83%
“…Molecular dynamics simulation mainly focuses on calculating the natural dynamics of biomolecular structures on the different timescale in a solution. This also helps calculate each atom's fluid properties and movement in a system in a given set of times 43 . So, the selected protein–ligand complexes of both MPXV proteins were observed to understand the stability of the complex under 300 ns MD simulation.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach has been used by the previous study which uses the FDA approved drugs against the three different targets such as topoisomerase1, p37, and thymidylate kinase of the monkey pox virus (Srivastava et al, 2023). Another study used drug screening against monkey pox virus cysteine proteinase (Odhar, 2022). The drugs IDs, 2D structures, name and docking score are shown in Table 1.…”
Section: Figurementioning
confidence: 99%